Peran Mediasi Kepercayaan pada Kausalitas Promosi dan Citra Merek dengan Loyalitas - I Wayan Rediyasa; I Putu Utama; I Made Ramia Adnyana; I Putu Eka Nila Kencana (JURNAL BISNIS HOSPITALITI, 2022)
Traditionally, promotion and the image of a business are believed to be the determinants of customer loyalty with trust acting as a mediator in the relationship that occurs. This article aims to determine the role of training participants' trust in the Course and Training Institute (LKP) on their loyalty to the institution as an influence of the promotion and image of the training institution that was built. With a survey approach, 300 participants in the Bali Gianyar LKP Overseas Training Center (OTC) training were chosen randomly as respondents. Structural equation model (SEM) was used to examine the model by showing the results of a positive and significant direct effect of promotion and image on the trust of the trainees with path coefficient values of 0.305 and 0.583, respectively. Variables that affect the loyalty of trainees, only the image that is proven to significantly affect loyalty with a path coefficient of 0.357, smaller than the effect of the training participants' trust of 0.495 which also proved significant. Through the mediation of the trust variable, the insignificant effect of promotion on trainee loyalty turned into a significant influence with a coefficient of 0.151.